2006
DOI: 10.1182/blood-2006-05-026203
|View full text |Cite
|
Sign up to set email alerts
|

Syk-dependent mTOR activation in follicular lymphoma cells

Abstract: The mammalian target of rapamycin (mTOR) is emerging as a promising target for antitumor therapy. However, the mechanism that contributes to its regulation in B lymphomas remains unknown. This study shows that in follicular lymphoma (FL) cells, mTOR is active because the cells displayed rapamycinsensitive phosphorylation of p70S6 kinase and 4E-BP1. Moreover, immunohistochemistry applied on lymph node tissue sections obtained from patients with FL revealed that, in most cases, p70S6 kinase was highly phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 50 publications
12
130
1
Order By: Relevance
“…In particular, they found that mTOR is activated in germinal centre cells and in the interfollicular areas, but not in the resting lymphocytes of the benign HIV-associated lymphadenopathy. Along with the reported occurrence of mTOR activation in non-HIV-associated lymphomas [56], these data suggest that the use of mTOR inhibitors could have potential therapeutic effects in HIV-associated and non-HIV-associated lymphomas. Although large studies to support the potential use of mTOR inhibitors against HIV-associated lymphomas are not available, it is interesting to observe that post-transplant lymphoproliferative disorder (PTLD)-type cell lines are highly sensitive to mTOR inhibition [57] and that substitution of immunosuppressive therapies based on inhibitors of calcineurin with mTORinhibitor-based therapies in organ-transplanted patients reduced the occurrence of PTLD lesions [58].…”
Section: Lymphomassupporting
confidence: 52%
“…In particular, they found that mTOR is activated in germinal centre cells and in the interfollicular areas, but not in the resting lymphocytes of the benign HIV-associated lymphadenopathy. Along with the reported occurrence of mTOR activation in non-HIV-associated lymphomas [56], these data suggest that the use of mTOR inhibitors could have potential therapeutic effects in HIV-associated and non-HIV-associated lymphomas. Although large studies to support the potential use of mTOR inhibitors against HIV-associated lymphomas are not available, it is interesting to observe that post-transplant lymphoproliferative disorder (PTLD)-type cell lines are highly sensitive to mTOR inhibition [57] and that substitution of immunosuppressive therapies based on inhibitors of calcineurin with mTORinhibitor-based therapies in organ-transplanted patients reduced the occurrence of PTLD lesions [58].…”
Section: Lymphomassupporting
confidence: 52%
“…161,163,164 As mentioned before the Rheb GTPase is an activator of mTORC1. Rheb is highly expressed in some human lymphomas 31,[165][166][167] and other cancers. 168 Rheb activity is dependent on farnesylation.…”
Section: Tsc2/rheb/mtorc1 Translation Initiation/elongation and Leukemiamentioning
confidence: 99%
“…These include drugs that target Notch, MAP kinase interacting kinase (MNK), the tyrosine kinase Syk, and aurora kinase. [117][118][119][120] 4. Targeting PI3K/AKT/mTOR in Pediatric Hematologic Malignancies…”
Section: Other Agents That Target the P13k/akt/mtor Pathwaymentioning
confidence: 99%